Instrumental Drives in English Learning Among Non-English Majors - Anjelina, Nuria; Rohani, Tri; Kalsum, Umi (Academia Open, 2025)
General Background: Motivation is a fundamental factor influencing success in foreign language learning, especially in contexts where English is a secondary academic subject. Specific Background: In Indonesia, non-English major students in smaller teacher training institutions often receive less attention in language motivation research. Knowledge Gap: Previous studies have largely focused on English majors or students from urban universities, leaving a lack of insight into motivation among non-English majors in peripheral regions. Aim: This study investigates the types and factors of English learning motivation among non-English major students at STKIP Muhammadiyah Pagar Alam. Results: Using a mixed-methods approach, findings reveal that most students demonstrate high extrinsic motivation—such as academic and career goals—while a smaller group, mainly from the Indonesian Language Education program, also show intrinsic interests like cultural appreciation and personal enjoyment. Novelty: This research highlights motivation dynamics in an underrepresented population, offering context-specific insights beyond mainstream university settings. Implications: The results suggest that English instruction in similar institutions should be tailored to students’ dominant motivational drivers, using student-centered methods and digital tools to foster engagement and overcome learning anxieties. Highlight : Non-English major students are generally motivated to learn English, mostly due to instrumental reasons like academic and career goals. Intrinsic motivation is more common among Indonesian Language students, who show interest in English media and global culture. Supportive learning environments—with interactive methods and digital tools—can boost motivation and reduce learning barriers. Keywords : English Learning, Motivation, Non-English Major Students, Integrative Motivation, Instrumental Motivation